2014
DOI: 10.18488/journal.79/2014.1.2/79.2.77.92
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology in Classroom Situations in Rural and Urban Areas in Zimbabwe: A Comparative Study on the Use of Digital and Projected Media in Teaching and Learning at Six Secondary Schools in Masvingo

Abstract: Information and communication technology have taken centre stage of almost every interaction, communication and learning processes among people of this world. This study is a comparative analysis of the usefulness of modern information and communication technology (ICT) in the transmission Review of Information Engineering and Applications Contribution/ OriginalityThe overall aim of this study is to contribute a theoretical framework that will help towards the generation, development and use of ICTs and projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…This demonstrates that, regardless of their location, secondary school students can watch and enjoy videos. However, the findings contrast with research conducted by [15] in Masvingo, Zimbabwe, which found that students in city areas reported significantly higher levels of video usage than students in rural areas where computers were nothing more than decorations. There are several possible reasons for this discrepancy in the findings.…”
Section: Resultscontrasting
confidence: 99%
“…This demonstrates that, regardless of their location, secondary school students can watch and enjoy videos. However, the findings contrast with research conducted by [15] in Masvingo, Zimbabwe, which found that students in city areas reported significantly higher levels of video usage than students in rural areas where computers were nothing more than decorations. There are several possible reasons for this discrepancy in the findings.…”
Section: Resultscontrasting
confidence: 99%